Back Cover: Recent progress on pure organic room temperature phosphorescent polymers. Issue 4 (31st August 2021) - Gao, Hao; Ma, Xiang
Abstract : Pure organic room temperature phosphorescence (RTP) polymers are developing rapidly and receiving widespread attention. The organic polymer hosts with their intertwined rigid network structure, just like the spider web, strongly suppress the molecular vibration of the phosphors and hinder the non‐radiative transition of triplet excitons, thereby enhancing emission. ( Aggregate . 2021;2:e38 )